Ultrasound in diagnosis of nontraumatic lower extremity pain syndromes: Case report - Giokits Kakavouli Giasna; Živanović Sandra (Vojnosanitetski Pregled)
Introduction. Musculoskeletal impairment is the most prevalent impairment in people over 65. The spine involvement is the most frequently reported. However, common regional pain syndromes usually arise from undefined mechanical, musculoskeletal or soft tissue disturbances. Use of imaging methods is becoming a mandatory tool in the clinical practice in order to achieve the prompt and accurate disease definition. Case report. The Caucasian 79-year-old-male patient attended with the history of an acute, piercing pain along the postero-medial side of the right Achilles tendon and the medial side of the right sole. According to the spine magnetic resonance imaging, X-rays and electrodiagnostic studies, diagnoses of the radicular, neurogenic pain and plantar fasciitis was suspected. However, the popliteal groove ultrasound assessment revealed the presence of hypertrophied semimembranosus- gastrocnemius bursa, compressing the popliteal neurovascular bundle. Conclusion. In patients with a symptomatology of peripheral neuropathy, use of imaging techniques such as ultrasound may be essential for accomplishing patients’ diagnostic approach.